(untitled) (Interdisciplinary Studies Journal, 2025)
This text, in continuation of a work path that we have been building, developing and improving every year, materializes our experience report on the coordination of the Working Group (WG 4) Education and new paradigms for a changing world: sharing and (re)thinking educational practice and institutional challenges, in its second edition, at the X Multidisciplinary Humanistic Meeting and IX Latin American Congress of Multidisciplinary Humanistic Studies. Inspired by the challenges experienced in our educational institutions and in our classrooms, in view of the new paradigms for a changing world, the WG proposed a space for dialogue, as a moment of reflection on pedagogical action and the social and institutional demands for review and reorganization of teaching processes. Resuming Freire’s premises, we seek to build a diverse, productive and formative path to inspire and/or improve new practices in different contexts, enriching the possibilities for renewal of the educational process, professionals and educational institutions. We have 44 proposals that, in some way, contemplate the relationship between education and society, from the perspective of civic and humanistic training, aware that education is a form of intervention in society.